The role of a structured intervention on the rational prescribing and deprescribing of benzodiazedpines in geriatric population in primary care - Duarte, Carlos Alexandre de Seiça Cardoso (2020)
Dissertação de Mestrado em Geriatria apresentada à Faculdade de Medicina